STRATEGI PENINGKATAN PROGRAM PEMBINAAN KEMANDIRIAN KULINER (DONAT) SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN NARAPIDANA DI RUTAN KELAS IIA YOGYAKARTA - Ardhian Kurniawan; Vivi Sylviani Biafri (Jurnal Komunikasi Hukum, 2024)
This research aims to analyze strategies for enhancing the culinary independence development program, specifically donuts, in order to improve the welfare of inmates at the Class IIA Yogyakarta Prison. This rehabilitation program is designed to provide skills to inmates so that they can be self-sufficient and earn an income during their incarceration. This research uses a qualitative method with a case study approach, where data is obtained through interviews, observations, and documentation. Research results show that although the donut culinary program has great potential in positively impacting the welfare of inmates, active participation from the inmates is still low. Some of the challenges faced include limited resources and the lack of interest from inmates to participate in this program. Therefore, a program enhancement strategy is needed through improved management, upgraded facilities, and more effective outreach to attract more inmates. Thus, this independence training program can contribute more optimally to the improvement of the welfare of prisoners during their incarceration.